Cyberspace and international relations : theory, prospects and challenges - Kremer, Jan-Frederik; Muller, Benedikt (Berlin : Springer, 2014)
'Cyberspace is everywhere in today's world and has significant implications not only for global economic activity, but also for international politics and transnational social relations. This compilation addresses for the first time the'cyberization' of international relations -- the growing dependence of actors in IR on the infrastructure and instruments of the Internet, and the penetration of cyberspace into all fields of their activities. The volume approaches this topical issue in a comprehensive and interdisciplinary fashion, bringing together scholars from disciplines such as IR, security studies, ICT studies and philosophy as well as experts from everyday cyber-space.' -- Publisher
Includes bibliographical references and index.
Keywords: Internet and international relations; Internet -- Political aspects